Strengthening access to and confidence in COVID-19 vaccines among equity-deserving populations across Canada: An exploratory qualitative study - Kainat Bashir; Mariame O. Ouedraogo; Christoffer Dharma; Mercedes Sobers; Vajini Atukorale; Dane Mauer-Vakil; Anushka Ataullahjan; Shaza A. Fadel; Sara Allin (PLoS ONE, 2026)
Introduction There is a need to reflect on the COVID-19 vaccine distribution plans across Canada and the extent to which they considered equity-deserving populations, as lessons from the rollout can inform future emergency responses and foster trust in public health. This paper examined and compared strategies implemented by six Canadian provinces to increase access and promote the uptake of COVID-19 vaccines among selected priority populations. We also explored the factors that impacted the implementation of these strategies. Methods In six provinces (Alberta, British Columbia, Manitoba, Nova Scotia, Ontario, and Quebec), we conducted an environmental scan of provincial rollout documents and media sources reporting vaccine distribution among selected priority populations: First Nations, Inuit, and Métis; Black communities; essential workers; people experiencing homelessness; and people with disabilities. We subsequently interviewed 39 key informants to validate the environmental scan results, identify additional strategies to increase COVID-19 vaccine uptake, and uncover perceptions of the facilitators and challenges that influenced the strategies implementation. Results We identified that provincial health authorities employed several strategies to overcome structural, geographical, and attitudinal barriers to COVID-19 vaccines experienced by the priority populations. Most provinces implemented walk-in, mobile, and pop-up vaccination clinics, mobilized their public and private health workforce, and designed multilingual communication materials. Facilitators in implementing COVID-19 vaccination strategies included harmonizing communication efforts, leveraging existing relationships and networks, and ensuring representation and leadership of community partners. Challenges to implementing COVID-19 vaccination strategies included uncoordinated communication efforts, inadequate distribution of vaccines to areas with the greatest need, mistrust in the government and healthcare system, vaccine hesitancy, and lack of cultural competence by vaccine providers. Conclusions This study highlights the divide between well-intentioned strategies and interventions and the reality of on-the-ground implementation. The findings offer valuable insights and can inform the implementation of strategies to distribute vaccines equitably in future large-scale vaccination efforts in Canada and globally.